Memorandum on social insurance and allied services in their bearing on neurotic disorder
1943 1943 1940s 19 pages The question of predisposition is also important ; it must be remembered that despite these handicaps, by far the majority of accidents do not result in neuroses. But the proposed changes which should lessen the tendency to neurosis, i.e., placing the main emphasis on treatment and rehabilitation, and restricting payments to the elimination of real want during the disability, should also improve the scheme for all facing the risk of injury. (b) Lump Sum Payments. "The experience of the Ministry of Pensions after the last war contradicted the assumption that lump sum settlements cured a post-traumatic neurotic state. At that time the problem was regarded as a purposive compensation neurosis. Indeed the payment of lump sum compensation as a weapon of recovery is completely discredited by those in a position to observe the subsequent history of the cases concerned, and in many countries is absolutely prohibited..." (Wilson and Levy, 1939). This point is also emphasized by Narcross (1935) in the U.S.A., where he investigated 320 compensation cases three years after settlement by lump sum. 67 had shown marked neurotic traits at the time of settlement and only one had made a complete recovery at the follow-up. Of the rest: 22 were at work, but earnings were down by 40 per cent. 22 were at work, but earnings were down by 60 per cent. 22 had deteriorated substantially and were unemployed. Opposite opinions have been stated, but no adequate follow-up study of lump sum cases made. Lump sums may be justified when they may be useful for rehabilitation into work, e.g. to purchase a business, etc., but if they are to be so allowed for this purpose careful safeguards would be needed to ensure that this purpose is fulfilled, otherwise the individual may eventually fall back on the benefits of the scheme and no advantage will have been served. There is no doubt that many psychiatric conditions have arisen owing to the legal machinery that pervades the supervision of Workmen's Compensation claims. Brain and other writers have advocated the establishment of ad hoc tribunals to assess medical evidence, which would no longer be the subject of cross-examination in the Court. Although much litigation will be removed under the Beveridge scheme, questions at common law will presumably continue to be dealt with as heretofore. Under such circumstances, medical tribunals would have a valuable part to play ; similar bodies have dealt successfully with service pensions since the Four Years War. (c) Employers' Payments. In the past employer-employee relationships have been adversely influenced by legal wrangling over compensation cases, and the removal of this potential source of friction into the realms of the social services should lessen the tendency to neurosis. The Beveridge plan envisages a special levy on hazardous industries, and 292/847/2/174